Influence of rotation speed on the corrosion behavior of friction stir welded joints in AZ31 magnesium alloy - Ziru Zhou; Shujin Chen; Michael Hodgson; Wei Gao; Yuxin Wang (Journal of Materials Research and Technology)
The purpose of this paper is to study the effect of friction stir welding (FSW) process conditions on the corrosion properties of AZ31 magnesium alloy welded joints. The effects of different rotation speeds on the microstructure and corrosion behavior of welded joints were studied by potentiodynamic polarization (Tafel plot), electrochemical impedance spectroscopy (EIS), and scanning vibrating electrode technique (SVET). The results demonstrate that rotational speed plays a pivotal role in determining the microstructure and corrosion resistance of AZ31 alloy welded joints. The joints processed at a rotational speed of 1800 r/min exhibited superior corrosion resistance, as evidenced by their performance in macro-electrochemical, micro-electrochemical, and salt spray experiments, indicating the most optimal corrosion resistance among the tested samples. This phenomenon results from the small grain structure and finer Al–Mn compounds formed during welding, influenced by heat and mechanical action under specific conditions.